2010
DOI: 10.3390/molecules15085445
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Butyl- and Phenylstannoxanes Derivedfrom 2-, 3- and 4-Pyridinecarboxylic Acids

Abstract: In vitro antioxidant activity for 12 stannoxanes derived from Ph3SnCl (compounds 1-3), Ph2SnCl2 (compounds 4-6), Bu3SnCl (compounds 7-9), and Bu2SnCl2 (compounds 10-12), was assayed qualitatively by the chromatographic profile with 1,1-diphenyl-2-picrylhydrazil (DPPH) method and by two quantitative methods: the DPPH radical scavenging activity and Ferric-Reducing Antioxidant Power (FRAP) assays. The results were compared with those obtained with the starting materials 2-pyridine- carboxylic acid (I), 3-pyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 37 publications
1
38
0
1
Order By: Relevance
“…The highest antiradical activity of MOXÀ Sn(II) complex may be correlated to its hydrogen donating ability as discussed by Corona-Bustamante et al [47] and Sakr et al [48] It is of interest to refer to the possible relation between the high antioxidant activity of MOXÀ Sn(II) complex and its low antimicrobial activity where the oxygenated compounds, in general, can attribute to the destroying of the microbial cell wall composition and thus increase the permeability of cytoplasm fluid. [42,49] Few studies showed that there is a sort of correlation between antioxidant and antimicrobial capacities of different substances.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…The highest antiradical activity of MOXÀ Sn(II) complex may be correlated to its hydrogen donating ability as discussed by Corona-Bustamante et al [47] and Sakr et al [48] It is of interest to refer to the possible relation between the high antioxidant activity of MOXÀ Sn(II) complex and its low antimicrobial activity where the oxygenated compounds, in general, can attribute to the destroying of the microbial cell wall composition and thus increase the permeability of cytoplasm fluid. [42,49] Few studies showed that there is a sort of correlation between antioxidant and antimicrobial capacities of different substances.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…In the past two decades, the properties of Schiff base metal complexes have stimulated a high degree of interest for their noteworthy contributions to single molecule-based magnetism; material science [4]; catalysis of many reactions, such as carbonylation, hydroformylation, oxidation, reduction and epoxidation [5]; industrial applications [6]; and complexing ability towards some toxic metals [7]. The interest in Schiff base compounds as analytical reagents is increasing because they enable the simple and inexpensive determination of different organic and inorganic substances [8]. The transition metal complexes of 4-aminoantipyrine and its derivatives have been examined extensively due to their wide biological, analytical and therapeutic applications in various fields [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The free radical‐scavenging activity of ligand and complexes is measured in terms of hydrogen donating or radical scavenging ability using the stable DPPH radical by the Blois method . The stock solutions of the ligand and complexes (100 μg/ml) were prepared in DMSO and their different concentrations (20–140 μL) were then prepared.…”
Section: Methodsmentioning
confidence: 93%
“…The antioxidant activity of the ligand, (I) and (II) studied by DPPH method at 20 μL‐ 140 μL showed scavenging potential (∼19–43.21%), (∼22.97–47.53%) and (∼26.91–50.39%) respectively (Figure ) (Table ) substantiating the fact that complexation leads to enhanced antioxidant activity . The discoloration from purple DPPH radical solution to yellow may be ascribed to hydrogen donation from the N‐H group in line with earlier reports on different metals (Scheme ).…”
Section: Decomposition Kineticsmentioning
confidence: 99%